The Covid 19 pandemic and the attitudes of consumers of agritourism farms towards health and physical activity - Poczta, Joanna Martyna (Journal of Education, Health and Sport, 2023)
The Covid 19 pandemic had a negative impact on various spheres of human life and the economy. Among them, tourism is mentioned, and mass tourism in particular. However, agritourism activity as a branch of the tourism sector is specific. Therefore, from the scientific and practical point of view, it turned out to be important to examine its impact on the behavior of consumers of agritourism services. From the point of view of tourists, agritourism has become an alternative to large clusters of people in popular, well-known, crowded destinations. Therefore, the following research questions arose: have the preferences of tourists regarding the place of rest changed under the influence of the Covid 19 pandemic and have the behavior of consumers of agritourism services changed in the context of physical activity and approach to health? The main purpose of this study is to investigate the influence of Covid 19 pandemic on consumers of agricultural farms in the context of health and physical activity in the hosts opinion. Research using the diagnostic survey method was carried out among the hosts of 60 agritourism farms in the Greater Poland Voivodeship in 2022. The results showed that although the hosts noticed a greater interest in agritourism and leisure in rural areas, they did not notice an increase in interest in physical activity and care for the health of their guests in connection with the Covid 19 pandemic.